answer question with photos
Attachments:
![](https://hi-static.z-dn.net/files/df4/b41f03ba9ee54463ca2ac327fbf8a210.jpg)
Answers
Answered by
2
Step-by-step explanation:
...........................
Attachments:
![](https://hi-static.z-dn.net/files/de3/f39ee1b01c7c039e4ed5757306433767.jpg)
Answered by
7
We know that, (a - b)(a + b) = a² - b²
Here a = x, b = y
By substituting the values in the above identity we have,
We know that, (a - b)(a + b) = a² - b²
Here a = x² , b = y²
By substituting the values in the above identity we have,
We know that, (a - b)(a + b) = a² - b²
Here
By substituting the values in the above identity we have,
(a - b)(a + b) = a² - b²
[1] (x + y)² = x² + y² + 2xy
[2] (x - y)² = x² + y² - 2xy
[3] (x + y)(x - y) = x² - y²
[4] (x + a)(x + b) = x² + (a + b)x + ab
(x + y)(x - y) = x² - y² or (x - y)(x -
+ y) = x² - y² both are same.
vibhanshu8441:
answer my qestion pls I had asked just now
Similar questions